Transitional Shelter - Shiozaki, Yoshimitsu; Tanaka, Yasuo; Hokugo, Akihiko; Bettencourt, Sofia (World Bank, Washington, DC, 2013)
Transitional shelter can play a crucial role in housing reconstruction following a mega disaster. Reconstruction of permanent housing cannot move forward until a number of complex issues are settled, such as relocation planning and removal of debris. Even after plans are agreed on and reconstruction begins, it may take several years for permanent housing to be completed. In this context, affected people may need to rely on transitional shelter for extended periods of time, and this will have a significant effect not only on housing, but also on their overall recovery including livelihood rehabilitation. This report gives findings; lessons; and recommendations for developing countries.